Implementasi Program Inovasi Peningkatan Nilai Produk Olahan Limbah Organik Tempurung Kelapa di Desa Wisata Tinalah Kulon Progo - Irawati, Novi; Zumar Rahafuna, Muhammad; Pribudi, Anggarani; Prasetyo, Hendi (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Tinalah Tourism Village, Kulon Progo, has significant potential in utilizing local resources, including coconut shells, which have traditionally been considered waste. This community service program aims to increase the added value of coconut shells through product innovation in the form of handicrafts and other creative products that support the village's tourism identity. Implementation methods include outreach, training, production assistance, and digital-based marketing. The results of the activity show improved skills among residents in processing coconut shells, the creation of new products with economic value, and increased tourist interest in local souvenirs. This program supports the concept of a circular economy, community empowerment, and the development of sustainable tourism villages.